2005
DOI: 10.1086/426871
|View full text |Cite
|
Sign up to set email alerts
|

Malaria‐Filaria Coinfection in Mice Makes Malarial Disease More Severe unless Filarial Infection Achieves Patency

Abstract: Coinfections are common in natural populations, and the literature suggests that helminth coinfection readily affects how the immune system manages malaria. For example, type 1-dependent control of malaria parasitemia might be impaired by the type 2 milieu of preexisting helminth infection. Alternatively, immunomodulatory effects of helminths might affect the likelihood of malarial immunopathology. Using rodent models of lymphatic filariasis (Litomosoides sigmodontis) and noncerebral malaria (clone AS Plasmodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 70 publications
2
141
3
Order By: Relevance
“…Whenever possible, evidence was taken from the coinfection studies themselves. Helminths in genera Fasciola (43), Heligmosomoides (44), Nippostrongylus (45), Schistosoma (46), and Trichinella (47) were considered to alter RBC availability, whereas helminths in genera Echinostoma (48), Litomosoides (49), and Taenia (50) were not. In equivocal cases [e.g., Trichinella, which alters RBC availability by suppressing erythropoiesis rather than destroying mature RBCs (47)], statisti-cal analysis was used to confirm that conclusions were robust to categorical reassignment.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever possible, evidence was taken from the coinfection studies themselves. Helminths in genera Fasciola (43), Heligmosomoides (44), Nippostrongylus (45), Schistosoma (46), and Trichinella (47) were considered to alter RBC availability, whereas helminths in genera Echinostoma (48), Litomosoides (49), and Taenia (50) were not. In equivocal cases [e.g., Trichinella, which alters RBC availability by suppressing erythropoiesis rather than destroying mature RBCs (47)], statisti-cal analysis was used to confirm that conclusions were robust to categorical reassignment.…”
Section: Methodsmentioning
confidence: 99%
“…Independent studies in Thailand and Senegal demonstrated that individuals harboring helminth parasites have a higher risk of malaria attack than individuals who are worm-free (27,34). A recent study showed that mice coinfected with the filarial parasite Litomosoides sigmodontis and blood-stage Plasmodium chabaudi had more severe malaria disease than mice infected with malaria alone had (17). These observations indicate that a preexisting helminth infection strongly modulates the development of immune protection and immunopathology in the host following a primary malarial infection.…”
mentioning
confidence: 99%
“…In this sense, theory predicts that multiple infections could be especially injurious for hosts, leading to anaemia, loss of body mass and reduced survival (Graham et al, 2005;Davidar & Morton, 2006). Such effects of malaria double infections have been poorly investigated and the reported results are inconclusive.…”
Section: Pathogenicity Of Avian Malaria Parasitesmentioning
confidence: 99%